The Effects of Aniline Concentration and Deposition Time on Polyaniline Conductance as Substrate in Fe/Ni Electrodeposition - Sutrisno, Mega; Paristiowati, Maria; Nailah Fauziyyah (Chemistry and Materials, 2022)
The research aims to determine the influence of aniline concentration and deposition time on the characteristics of polyaniline prepared using potentiostatic and galvanostatic electrodeposition methods. FTIR characterization data shows the typical peak of polyaniline in the form of the presence of a quinoid functional group at a wavenumber of 1596.16 cm-1. The typical diffraction pattern of polyaniline using XRD was detected at peaks of 2θ 21.1007o and 23.5995o. Polyaniline formed using SEM has a surface morphology that grows in a stacked and irregular manner and has a high conductance value so that it can be used as a substrate in Fe/Ni electrodeposition. The results of the Fe/Ni electrodeposition process when viewed using SEM cause the polyaniline surface morphology to be covered by a Fe/Ni alloy by having an elemental composition from the EDS test data, are iron (Fe) 68.15% and nickel (Ni) 24.83%. Fe/Ni levels from AAS data attached to PANI(pot)-Fe/Ni are 1.1912 ppm and 0.8288 ppm; in PANI(gal)-Fe/Ni are 1.2219 ppm and 0.8392 ppm.